(untitled) (Journal of Organizational Psychology, 2020)
As contemporary organisations strive to survive, grow and make a profit, it is critical they adopt best practices and high-involvement management that can guarantee superior organisational performance. The objective of this study is to evaluate the moderating effect of work engagement on high performance work systems and psychological ownership. Survey data from 302 employees working in the telecommunication industry in Ghana indicate that high-performance work systems is positively associated with psychological ownership. The results of the research also revealed that there is a positive association between work engagement and psychological ownership. As such, work engagement effectively moderates the relationship between high performance work systems and psychological ownership. Implications of our findings for research and practice are presented.